2013
DOI: 10.1002/jbm.b.32943
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the compressive strength of a cuttlefish bone‐derived porous hydroxyapatite scaffold via polycaprolactone coating

Abstract: Cuttlefish bones (CBs) have emerged as attractive biomaterials because of their porous structure and components that can be converted into hydroxyapatite (HAp) via a hydrothermal reaction. However, their brittleness and low strength restrict their application in bone tissue engineering. Therefore, to improve the compressive strength of the scaffold following hydrothermal conversion to a HAp form of CB (CB-HAp), the scaffold was coated using a polycaprolactone (PCL) polymer at various concentrations. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…The compressive strength decreased with the HT due to a more extensive degradation of the organic matter that provides the mechanical support of the structure, however, with exception of the coating with 1% PCL, the compressive strength improved with the PCL coating as reported in Table 2. The coated scaffolds did not exhibit any cytotoxicity, cells were able to adhere and proliferate and also it was demonstrated that penetration of cell happened through the entire depth of the scaffold [206,209]. The cell proliferation was higher for the sample coated with 1% PCL.…”
Section: Cuttlefish Bonementioning
confidence: 90%
See 4 more Smart Citations
“…The compressive strength decreased with the HT due to a more extensive degradation of the organic matter that provides the mechanical support of the structure, however, with exception of the coating with 1% PCL, the compressive strength improved with the PCL coating as reported in Table 2. The coated scaffolds did not exhibit any cytotoxicity, cells were able to adhere and proliferate and also it was demonstrated that penetration of cell happened through the entire depth of the scaffold [206,209]. The cell proliferation was higher for the sample coated with 1% PCL.…”
Section: Cuttlefish Bonementioning
confidence: 90%
“…Composite materials derived from CB CaP scaffolds obtained from CB are normally brittle and exhibited low strength, thereby limiting the application of these materials as bone grafts. In order to improve the compressive strength, some authors investigated the coating of these scaffolds with polymers like PCL [206][207][208][209], polyvinyl alcohol [207] and collagen [210].…”
Section: Cuttlefish Bonementioning
confidence: 99%
See 3 more Smart Citations